2014
DOI: 10.1590/0104-1169.3305.2416
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia: occurrence and management in women with breast cancer receiving chemotherapy

Abstract: Objectives to identify the prevalence, and describe the management of, neutropenia throughout the chemotherapy treatment among women with breast cancer. Methods observational study, cycles of chemotherapy. 116 neutropenic events were recorded, and 63.3% of the patients presented neutropenia at some point of their treatment, 46.5% of these presenting grade II. The management used was temporary suspension between the cycles and the mean number of delays was 6 days. The study was prospective and longitudinal, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
5
1
3
Order By: Relevance
“…A study on the occurrence and management of neutropenia in women with breast cancer is in line with the results of this research, regarding the need for nursing empowerment in the care of these patients, also revealing that nurses can contribute for patients to perform treatment according to the stipulated schedule, through the standardization of care, promotion of the use of colony stimulating factor and assistance in clinical decision making (27) .…”
Section: Discussionsupporting
confidence: 77%
“…A study on the occurrence and management of neutropenia in women with breast cancer is in line with the results of this research, regarding the need for nursing empowerment in the care of these patients, also revealing that nurses can contribute for patients to perform treatment according to the stipulated schedule, through the standardization of care, promotion of the use of colony stimulating factor and assistance in clinical decision making (27) .…”
Section: Discussionsupporting
confidence: 77%
“…The PRAXIS prospective multicentre study observed a 4.3% incidence of FN among 734 patients [22] and a European multinational neutropenia study that included 444 breast cancer patients reported an FN incidence of 6% [23]. Other recent single centre studies have even reported much higher values, with one Brazilian group reporting as high as a 63.3% [24] incidence of CIN (N = 79), a study from France with 524 breast cancer patients reported a 17% incidence of FN [25] and a UK study of 325 patients showing a 19% incidence of FN [26]. The risk of developing neutropenia during chemotherapy increased significantly with age, ECOG performance score of >1 and bone metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Although chemotherapy-induced neutropenia is most commonly associated with treatment of hematologic malignancies and conditioning regimens for HSCT, a number of regimens to treat solid tumors also cause neutropenia [74-77]. …”
Section: Introductionmentioning
confidence: 99%